Empire of Liberty - Hampf, Michaela M. (De Gruyter, 2020)
M. Michaela Hampf analyzes American history from the end of the Civil War to the epochal year 1898. She argues that the rise of the United States to become an imperial power had already begun in the years following 1865. The study takes new methodical approaches to explain America's special path, drawing upon the theory of path-dependency.